Preparation method and application of anode catalyst and membrane electrode

By using the binding of Pt3Fe alloy with HCNO and doping of Fe, the scarcity and CO poisoning of precious metal Pt in PEMFC are solved, reducing costs and improving the performance and tolerance of the catalyst, achieving efficient battery performance and stability sex.

CN119170808APending Publication Date: 2024-12-20NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410922454.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The scarcity of precious metal Pt and CO poisoning in existing proton exchange membrane fuel cells (PEMFCs) hinder their commercial development and are costly. How to reduce costs and improve the proton transport capability and CO tolerance of the catalyst still need to be Further research.

Method used

Pt-based binary alloy Pt3Fe is used as anode catalyst. Through the uniform binding of HCNO and Pt3Fe and the migration of a small amount of Pt3Fe, the proton transport capacity of the catalyst is enhanced, and the adsorption energy of Pt to CO is reduced through the introduction of Fe, thereby improving the stability of the catalyst and CO tolerance.

Benefits of technology

It has achieved the reduction of catalyst costs and improved battery performance, especially the peak power density and steady-state current density under H2-O2 and H2-Air conditions, significantly improving the CO tolerance of the catalyst, and the current density is in the CO poisoning test. Small attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170808A_ABST
    Figure CN119170808A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an anode catalyst and a membrane electrode, and the preparation method of the anode catalyst comprises the following steps: preparing KCa2Nb3O10 by a solid-phase synthesis method, and then carrying out acid replacement to obtain HCa2Nb3O10; pt3Fe / EC is prepared, the Pt3Fe / EC and HCa2Nb3O10 are mixed, ball-milled and dried, and the Pt3Fe / EC And dispersing the obtained anode catalyst, a Nafion solution and conductive carbon in an alcohol solution to prepare anode slurry, spraying the anode slurry on an electrolyte membrane, and performing hot pressing to obtain the membrane electrode. The Pt-based binary alloy is used for replacing pure Pt to serve as an anode carrier, so that the cost can be effectively reduced; the HCNO can be uniformly combined with the Pt3Fe / EC, and a small amount of Pt3Fe is migrated to the HCNO, so that the proton transmission capability of the catalyst is enhanced, and the battery performance is greatly improved; and due to the introduction of Fe, the adsorption energy of Pt to CO is reduced to a certain extent, so that the CO tolerance of the catalyst is improved, and the stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anode catalyst, a preparation method of a membrane electrode and applications thereof, and belongs to the technical field of proton exchange membrane fuel cells. Background Art

[0002] Proton exchange membrane fuel cells (PEMFC) are one of the most promising renewable energy technologies in the future. At present, precious metal Pt is the key raw material for the preparation of PEMFC anode catalysts, which is mainly due to the high electrocatalytic activity of precious metal Pt for hydrogen oxidation (HOR). However, precious metal Pt has low content, high cost and is prone to CO poisoning and deactivation. CO poisoning refers to the adsorption of CO on the Pt surface to block the hydrogen oxidation reaction. Therefore, the scarcity of Pt and the susceptibility to CO poisoning have hindered the further development of PEMFC commercialization. Therefore, in recent decades, researchers' research has been widely focused on reducing the amount of precious metal Pt and improving the catalyst activity at the same time.

[0003] Among them, many researchers doped a small amount of transition metals into the precious metal Pt to reduce the amount of Pt used. Compared with pure Pt, Pt alloys have higher activity, which is mainly due to the fact that the doping of transition metals improves the surface electrons and atomic structure of the precious metal Pt. Yu Dai, Yuwen Liua and Shengli Chena doped metal tungsten (W) into the precious metal Pt to synthesize nano-alloy Pt3W and PtW2 anode catalysts. W doping can significantly enhance the electrocatalytic activity of HOR, and its exchange current density is increased by nearly 4 times compared with pure Pt. In addition, compared with pure Pt, Pt-W alloy has weakened CO surface adsorption and has stronger CO tolerance.

[0004] Guoyu Shi, Hiroshi Yano et al. synthesized a new binary Pt alloy HOR catalyst, Pt 2AL -Pt-Fe / C, Pt 2AL -Pt-Co / C and Pt 2AL -Pt-Ni / C. Under the conditions of 70℃ and 0.1M perchloric acid (HClO4), Pt 2AL -Pt-Fe / C showed the highest mass activity (1127 A / g metal ), is a commercial Pt / C (563A / g metal ). 2AL -Pt-Co / C and Pt 2AL -Pt-Ni / C also has higher mass activity than commercial Pt / C. 2AL -Pt-Fe / C has the highest CO resistance activity and is much better than commercial Pt / C, which is due to the presence of the alloy reducing the adsorption strength of Pt for CO.

[0005] Hansung Kim's team used high-temperature heat treatment technology and polydopamine (PDA) protective coating method to prepare PtRuNi / C ternary electrocatalysts with composition gradient shells. During the high-temperature treatment process, Pt atoms moved to the surface of the catalyst, and Ru and Ni atoms gradually moved to the core of the particles due to the segregation energy difference. The internal Ru and Ni caused changes in the electronic state of Pt on the catalyst surface, enhancing the catalyst performance and CO resistance. Pt and Ru acted as a barrier to prevent Ni atoms from leaching in an acidic environment, thereby improving the stability of the catalyst. Under conditions containing a CO concentration of 10ppm, the current density of the ternary alloy at a voltage of 0.6V was 52% higher than that of commercial Pt / C. At present, some researchers have developed other non-Pt-based catalysts in the hope of replacing Pt-based catalysts.

[0006] Prasad Prakash Patel et al. synthesized the nano alloy catalyst Co-Ir by a two-step method. Compared with commercial Pt / C, Co 1-x Ir x The peak power density of (x=0.3 and 0.4) is increased by 40% and 85%, respectively.

[0007] However, further research is needed to provide an anode catalyst and membrane electrode that can enhance the proton transfer capacity and CO tolerance of the catalyst and reduce the cost. Summary of the invention

[0008] The purpose of the present invention is to provide an anode catalyst, a membrane electrode preparation method and application thereof, wherein a Pt-based binary alloy is used to replace pure Pt as an anode carrier, which can effectively reduce costs; HCNO can be uniformly combined with Pt3Fe / EC, and a small amount of Pt3Fe migrates to HCNO, thereby enhancing the proton transport capacity of the catalyst and greatly improving the battery performance; the introduction of Fe also reduces the adsorption energy of Pt to CO to a certain extent, thereby increasing the CO tolerance of the catalyst and improving the stability of the battery.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] A method for preparing an anode catalyst, specifically: preparing KCa2Nb3O by solid phase synthesis 10 Then acid replacement was performed to obtain HCa2Nb3O 10 ; Prepare Pt3Fe / EC and react with HCa2Nb3O 10 The mixture is ball-milled and then dried to obtain the anode catalyst.

[0011] Preferably, KCa2Nb3O 10The preparation method is as follows: K2CO3, CaCO3 and Nb2O5 are mixed in a mass ratio of (0.5-1.2):(1.5-3):(3-6), ball milled at 200-500 rpm for 0.5-2h and then dried, calcined at 1000-1500°C for 10-15h, ground, and re-fired at 1000-1500°C to obtain.

[0012] Preferably, KCa2Nb3O 10 Acid replacement to obtain HCa2Nb3O 10 The specific method is: according to the ratio of (2-5) g: (80-150) ml, KCa2Nb3O 10 The product is immersed in 5-10 mol / L HCl at room temperature for 40-50 hours, and the HCl is replaced once every 20-25 hours, and then centrifuged and dried at 60-80°C.

[0013] Preferably, the preparation method of Pt3Fe / EC includes an impregnation method or a two-step method; wherein the specific method of the impregnation method is: dispersing ferric nitrate nonahydrate, chloroplatinic acid, and PVP in an EC aqueous solution, heating and stirring until dry, and calcining the obtained powder under a hydrogen and argon atmosphere to obtain Pt3Fe / EC;

[0014] The specific method of the two-step method is: disperse a Pt / C catalyst with a Pt content of 20-40wt% and ferric nitrate nonahydrate in deionized water, adjust the pH to 9-10.5 with ammonia water, and then centrifuge, dry, and calcine in a hydrogen and argon atmosphere to obtain Pt3Fe / EC.

[0015] Preferably, in the impregnation method, the ratio of ferric nitrate nonahydrate, chloroplatinic acid, PVP, EC and water is (20-30) mg: (7-12) ml: (100-150) mg: (50-70) mg: (20-50) ml, and the mass concentration of platinum in chloroplatinic acid is 2-7 mg Pt / ml;

[0016] The conditions for heating and stirring are: 70-90°C;

[0017] The calcination conditions are: 850-1000°C, 1.5-3h.

[0018] Preferably, in the two-step method, the ratio of Pt / C catalyst, ferric nitrate nonahydrate and deionized water is (180-250) mg: (45-60) mg: (30-80) ml;

[0019] Drying conditions: 60-80℃, 20-30h;

[0020] The calcination conditions are: 850-1000°C, 1.5-3h.

[0021] A method for preparing a membrane electrode comprises dispersing an anode catalyst prepared by any of the above methods, a 5wt% Nafion solution and conductive carbon in an alcohol solution in a mass ratio of 1:(5-8):(0.3-1.2) to prepare an anode slurry, and then spraying the anode slurry on an electrolyte membrane at 70-85°C and hot pressing to obtain the anode slurry.

[0022] The membrane electrode is used as an anode in a proton exchange membrane fuel cell.

[0023] The application of Fe doping in improving the CO tolerance of proton exchange membrane fuel cells is to dope Fe into the anode catalyst, adjust the electronic structure of Pt by Fe, and reduce the adsorption energy of Pt for CO to enhance the CO tolerance of the anode catalyst.

[0024] The beneficial effects of the present invention are:

[0025] 1. Pt3Fe / EC was synthesized by using binary alloy Pt3Fe instead of pure Pt in work 2, which reduced the amount of pure Pt and the catalyst cost;

[0026] 2. Under H2-O2 conditions, Pt3Fe / EC-HCNO exhibited 1.43W / cm at 0.45V. 2 The best peak power density is 1.06 and 1.09 times that of PtFe / EC-HCNO and Pt / C-HCNO. Under H2-Air conditions, Pt3Fe / EC-HCNO also exhibits the highest battery performance, with a peak power density of 907.5 mW / cm 2 . In addition, after 24h of constant voltage (0.6V) steady-state test, the current density of Pt3Fe / EC-HCNO only decayed by ≤3%. SEM, TEM and other characterization analyses of Pt3Fe / EC-HCNO revealed that HCNO could be uniformly combined with Pt3Fe / EC, and a small amount of Pt3Fe migrated to HCNO, enhancing the proton transport capacity of the catalyst;

[0027] 3. In the anti-CO poisoning test, after 100ppm H2 / CO mixed gas was continuously passed into the anode for 1h, the current density of Pt3Fe / EC-HCNO decreased by 85%, while the current density of Pt / C-HCNO decreased by 91%. This shows that the introduction of Fe reduces the adsorption energy of Pt to CO to a certain extent, thereby increasing the CO tolerance of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1One-step preparation of Pt3Fe / EC (a) HR-TEM morphology, (b) particle size distribution of alloy Pt3Fe, (c) lattice fringes of alloy Pt3Fe; two-step preparation of Pt3Fe / EC (d) HR-TEM morphology, (e) particle size distribution of alloy Pt3Fe, (f) lattice fringes of alloy Pt3Fe;

[0029] Figure 2 (a) XRD spectra of Pt3Fe / EC prepared by different synthesis methods, (b) single cell test results under H2-O2 conditions;

[0030] Figure 3 XRD spectra of PtFe / EC and Pt3Fe / EC with different metal ratios and further prepared PtFe / EC-HCNO and Pt3Fe / EC-HCNO;

[0031] Figure 4 (a, d) Single cell test results and peak power density bar graphs of different samples under H2-O2 conditions, (b, e) Single cell test results and peak power density bar graphs of different samples under H2-Air conditions, (c,

[0032] f) 24h constant voltage (0.6V) steady-state test of Pt3Fe / EC-HCNO and comparison sample Pt / C-HCNO and current density bar graph before and after the steady-state test;

[0033] Figure 5 (a) SEM image of Pt3Fe / EC-HCNO, (bc) THR-TEM images of the same position at different magnifications, (d) particle size distribution of Pt3Fe alloy, (e) lattice fringes of HCNO, (f) lattice fringes of Pt3Fe alloy;

[0034] Figure 6 The current density-time curves of different sample batteries when 100 ppm H2 / CO mixed gas is continuously introduced into the anode for 1 h (a, c) and the current density changes before and after the introduction of CO; (b, d) the single cell performance before and after anti-CO poisoning and the corresponding peak power density bar graphs. DETAILED DESCRIPTION

[0035] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.

[0036] Synthesis and Preparation of Pt3Fe / EC and PtFe / EC

[0037] Two methods were used to prepare Pt3Fe / EC. The first method was to synthesize Pt3Fe / EC by a simple impregnation method (referred to as the one-step method). First, 60 mg of EC (conductive carbon black, product model EC600JD) was dissolved in 30 ml of deionized water and ultrasonicated for 30 minutes. Subsequently, 25.21 mg of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 9.13 ml of chloroplatinic acid (H2PtCl6·6H2O) (4 mg Pt / mL), 120mg PVP (molecular weight 8000) were uniformly dispersed by ultrasonication for 30 minutes. After being uniformly dispersed, the mixed solution was poured into a beaker, heated and stirred at 80°C until dry, and the powder was collected. Finally, the collected powder was calcined at 900°C for 2h in a hydrogen and argon atmosphere to prepare Pt3Fe / EC.

[0038] The second method is to prepare Pt3Fe / EC by loading metal Fe on commercial platinum carbon Pt / C (JM, 40wt%) (referred to as the two-step method). First, Pt / C (200mg), 55.23mgFe(NO3)3·9H2O, and 50ml deionized water were mixed and ultrasonicated for 1h, and then the pH value was adjusted to 10 with ammonia water, and the precipitate was obtained by centrifugation, and dried in a vacuum drying oven at 70°C overnight to obtain the Pt3Fe / EC precursor. Finally, Pt3Fe / EC (with a Pt loading of 20%) was prepared by calcining at 900°C for 2h in a hydrogen and argon atmosphere.

[0039] The preparation method of PtFe / EC adopts the one-step synthesis mentioned above, and only needs to change the ratio of Pt to Fe, which will not be repeated here.

[0040] Synthesis and Preparation of Pt3Fe / EC-HCNO and PtFe / EC-HCNO

[0041] Layered perovskite KCa2Nb3O was synthesized by solid phase method. 10 (KCNO), K2CO3 (0.86 mg), CaCO3 (2.00 mg), Nb2O5 (3.99 mg) and an appropriate amount of deionized water were added to a ball mill, ball milled at 400 rpm for 1 hour, and then dried under a sodium lamp to obtain a precursor. The precursor was calcined in a high-temperature furnace at 1200°C for 12 hours, taken out and ground once, and then calcined for 12 hours to finally obtain KCNO.

[0042] Take 2.5g of KCNO and place it in 100ml of concentrated HCl (7mol / L) at room temperature for 48h, replace the concentrated HCl once every 24h, collect the white precipitate by centrifugation, and dry it in a vacuum oven at 70℃ overnight to obtain HCa2Nb3O 10 (HCNO).

[0043] Pour 100 mg HCNO, 100 mg Pt3Fe / EC and an appropriate amount of water into a ball mill and mill for 1 h. Dry the mixed solution under a sodium lamp to prepare Pt3Fe / EC-HCNO.

[0044] Preparation of membrane electrode

[0045] Pt3Fe / EC-HCNO or PtFe / EC-HCNO was used as the anode catalyst, commercial Pt / C (JM, 20 wt%) was used as the cathode, and the Pt loading of the anode and cathode was 0.2 mg, respectively. Pt / cm 2 and 0.09mg Pt / cm 2 . Take Pt3Fe / EC-HCNO or Pt3Fe / EC-HCNO (6 mg), 5wt% Nafion (41.93 mg) and SuperP (3.24 mg) and dissolve them in 2mL isopropanol and ultrasonically mix them as anode slurry. Similarly, take Pt / C (11 mg) and 5wt% Nafion (73.22 mg) and dissolve them in 1.5mL isopropanol and ultrasonically mix them as cathode slurry. At 75°C, the anode and cathode slurries are sprayed on the electrolyte membrane and prepared into membrane electrodes by hot pressing.

[0046] Preparation of Pt-Fe materials by different synthesis methods

[0047] Firstly, Pt3Fe / EC was prepared by two synthetic methods. Figure 1 The (ac) region is Pt3Fe / EC prepared by a one-step method, and the (bf) region is Pt3Fe / EC prepared by a two-step method. Figure 1 The alloy Pt3Fe in (area (a), area (b), area (d) and area (e)) is uniformly loaded on EC-600. The particle size distribution diagram shows that the Pt3Fe / EC particles prepared by the one-step method have a smaller particle size, mostly concentrated in the range of 2.2-2.6nm, while the particle size of the Pt3Fe / EC particles prepared by the two-step method is mostly concentrated between 3.1-3.8nm. This is because the two-step method loads metal Fe on the basis of Pt / C and sinters it again, which leads to particle regrowth and agglomeration. Figure 1 The middle (c) area is Pt3Fe / EC prepared by a one-step method, and its lattice spacing is 0.224nm, corresponding to the Pt3Fe(111) crystal plane. Figure 1 The lattice spacing of Pt3Fe / EC prepared by the two-step method in (f) is 0.224nm and 0.194nm, corresponding to the Pt3Fe(111) crystal plane and Pt3Fe(200) crystal plane, respectively, further proving that both synthesis methods can successfully prepare Pt3Fe / EC.

[0048] Figure 2The middle (a) area is the XRD pattern of Pt3Fe / EC prepared by two methods. The Pt3Fe / EC synthesized by the two methods are consistent with the standard PDF card (PDF#01-089-2050). Through XRD spectrum analysis, it is found that the diffraction peak of Pt3Fe / EC synthesized by the two-step method is sharper, indicating that the Pt3Fe / EC prepared by this method has higher crystallinity and larger particle size, which is caused by Pt3Fe / EC being calcined at high temperature twice.

[0049] Subsequently, Pt3Fe / EC synthesized by the two synthesis methods was physically mixed with HCNO to prepare Pt3Fe / EC-HCNO, and they were assembled into membrane electrodes for single cell testing under H2-O2 conditions. Figure 2 The middle (b) area is the battery performance diagram, in which the Pt3Fe / EC-HCNO prepared by one-step method reaches 1.43W / cm 2 The peak power density is 1.46 times that of the two-step method (977.5mW / cm 2 ), so a one-step method was used to prepare Pt3Fe / EC-HCNO.

[0050] Preparation of Pt-Fe materials with different metal ratios

[0051] Subsequently, the Pt-Fe ratio was further optimized, and Pt3Fe / EC and PtFe / EC were prepared by a one-step method, and then mixed with HCNO to prepare Pt3Fe / EC-HCNO and PtFe / EC-HCNO. Figure 3 The XRD patterns of Pt3Fe / EC, PtFe / EC, Pt3Fe / EC-HCNO, PtFe / EC-HCNO and HCNO show that the characteristic peaks at 40.312° and 46.892° correspond to the (111) and (200) crystal planes of Pt3Fe, and are consistent with the standard PDF card of Pt3Fe (PDF#01-089-2050). Similarly, the characteristic peaks at 40.599° and 46.472° correspond to the (111) and (200) crystal planes of PtFe, and are consistent with the standard PDF card of PtFe (PDF#01-089-2051). This proves that Pt3Fe / EC and PtFe / EC were successfully prepared. In addition, the phase structures of Pt3Fe / EC-HCNO and PtFe / EC-HCNO are basically consistent with HCNO, and obvious characteristic peaks of Pt3Fe and PtFe appear, which proves that both Pt3Fe / EC and PtFe / EC combine well with HCNO.

[0052] In order to further screen out the best metal ratio, Pt3Fe / EC-HCNO, PtFe / EC-HCNO and Pt / C-HCNO were sprayed on the anode, and commercial Pt / C was sprayed on the cathode and the anode loading was 0.1 mg. metal / cm 2 , cathode loading is 0.2 mg metal / cm 2 The film electrode was prepared. Subsequently, single cell tests were carried out under H2-O2 and H2-Air conditions. Figure 4 As shown in the (a) and (d) regions, under H2-O2 conditions, Pt3Fe / EC-HCNO exhibits the best battery performance with a peak power density of 1.43 W / cm 2 , which is 1.49 times that of commercial Pt / C (958.5mW / cm 2 ). However, the peak power density of PtFe / EC-HCNO under the same test conditions is 1.35 W / cm 2 , both of which are higher than the peak power density of Pt / C-HCNO in work 2 (1.31 W / cm 2 ). Figure 4 The middle (b) and (e) regions are single-cell tests conducted under H2-Air conditions. The battery performance of the three is Pt3Fe / EC-HCNO>PtFe / EC-HCNO>Pt / C-HCNO from high to low, with peak power densities of 907.5 mW / cm 2 、865mW / cm 2 and 847.5mW / cm 2 At a high voltage of 0.6 V, the current density of Pt3Fe / EC-HCNO is 1.3 A / cm 2 , respectively PtFe / EC-HCNO(1.17A / cm 2 ) and Pt / C-HCNO(1.16A / cm 2 ) by 1.11 and 1.12 times respectively. Subsequently, steady-state tests were carried out on Pt3Fe / EC-HCNO and Pt / C-HCNO with better performance under H2-O2 conditions ( Figure 4 The current density changes within 24 hours were detected by maintaining a constant potential of 0.6 V in the middle (c) and (f) regions. The current density decays of Pt3Fe / EC-HCNO and Pt / C-HCNO were both within 3%, showing good stability.

[0053] In summary, Pt3Fe / EC-HCNO prepared by a one-step method was finally used as the anode catalyst for PEMFC.

[0054] Subsequently, the Pt3Fe / EC-HCNO prepared by one-step method was characterized by SEM and TEM. Figure 4 The middle (a) area shows that HCNO and Pt3Fe / EC are mixed more evenly. Figure 4 The middle (d) area is the particle size distribution diagram of Pt3Fe. The particle size of Pt3Fe is mostly concentrated between 2-2.5nm, which is basically consistent with the particle size of Pt3Fe / EC. In addition, TEM was used to detect the existence of Pt3Fe, EC-600 and HCNO. It was found that most of Pt3Fe was uniformly loaded on EC-600, and a small amount was loaded on HCNO ( Figure 5 Further increasing the magnification of the transmission electron microscope will yield different lattice fringes, among which: Figure 5 The lattice spacing in the middle (e) region is 0.263 nm, which is consistent with the standard PDF card of HCNO (PDF#00-040-0884) and corresponds to the HCNO (104) crystal plane. Figure 5 The lattice spacing of 0.224 nm in the middle (f) region corresponds to the Pt3Fe(111) crystal plane, which is consistent with the PDF card (PDF#01-089-2050).

[0055] Test of Pt3Fe / EC-HCNO against CO poisoning

[0056] In order to verify whether Fe doping can increase the CO tolerance of the battery, Pt3Fe / EC-HCNO and Pt / C-HCNO were assembled into batteries for anti-CO poisoning experiments. The test was carried out at normal pressure, with H2 / CO (100ppm) mixed gas as the fuel gas at the anode and oxygen as the fuel gas at the cathode. Figure 6 The middle (a) and (c) areas show the change of current density with the duration of CO introduction. It is found that when CO is introduced for 1 h, the current density of Pt3Fe / EC-HCNO decreases by 85%, while the current density of Pt / C-HCNO decreases by 91%. Figure 6 The (b) and (d) regions are the battery performance comparison diagrams of Pt3Fe / EC-HCNO and Pt / C-HCNO before and after anti-CO poisoning. The peak power density of Pt3Fe / EC-HCNO before CO poisoning is 850mW / cm 2 The peak power density of Pt3Fe / EC-HCNO before and after CO poisoning was 800mW / cm 2 and 80mW / cm 2 , the power density dropped by 90%. This further proves that the introduction of Fe can adjust the electronic structure of Pt and reduce the adsorption energy of CO by the noble metal Pt, thereby enhancing the CO tolerance of the catalyst.

[0057] In summary, this embodiment mainly focuses on two major issues. One is that the scarcity of precious metal Pt leads to an increase in the cost of PEMFC catalysts, which hinders the commercial development of PEMFC. The other is that the anode fuel gas of PEMFC on the market is mostly gray hydrogen. Impurities such as CO contained in gray hydrogen can easily cause poisoning and deactivation of precious metal Pt catalysts. If green hydrogen is used, the cost will increase significantly. Therefore, in order to reduce the cost of the catalyst, the carrier was optimized, and Pt3Fe / EC was synthesized using the binary alloy Pt3Fe instead of pure Pt in Work 2. Then, Pt3Fe / EC-HCNO was synthesized. Fe doping can adjust the electronic structure of Pt to a certain extent, improve the HOR performance and reduce the adsorption energy of Pt to CO, thereby enhancing the CO tolerance of the catalyst. The specific contents are as follows:

[0058] (1) First, the two synthesis methods of Pt3Fe / EC were analyzed by XRD, SEM and battery performance. The Pt3Fe / EC prepared by the two methods has a good phase structure, but because the two-step method is an alloy formed by two high-temperature calcinations, the alloy particles grow larger, which affects the battery performance. Therefore, the one-step method was finally selected to prepare the catalyst.

[0059] (2) Subsequently, the effect of metal ratio on battery performance was investigated, and Pt3Fe / EC-HCNO and PtFe / EC-HCNO were prepared respectively. The two prepared catalysts were made into film electrodes for single cell testing. Among them, Pt3Fe / EC-HCNO exhibited 1.43W / cm at 0.45V under H2-O2 conditions. 2 The best peak power density is 1.06 and 1.09 times that of PtFe / EC-HCNO and Pt / C-HCNO. Under H2-Air conditions, Pt3Fe / EC-HCNO also exhibits the highest battery performance, with a peak power density of 907.5 mW / cm 2 . In addition, after 24h of constant voltage (0.6V) steady-state test, the current density of Pt3Fe / EC-HCNO only decayed by ≤3%. The selected Pt3Fe / EC-HCNO was characterized by SEM, TEM and other analysis, and it was found that HCNO can be evenly combined with Pt3Fe / EC, and a small amount of Pt3Fe migrates to HCNO, which enhances the proton transport ability of the catalyst.

[0060] (3) In order to verify that the loaded Pt3Fe has higher CO tolerance, Pt3Fe / EC-HCNO and Pt / C-HCNO were prepared into film electrodes and subjected to CO poisoning resistance tests. It was found that after 100ppm H2 / CO mixed gas was continuously passed into the anode for 1h, the current density of Pt3Fe / EC-HCNO decreased by 85%, while the current density of Pt / C-HCNO decreased by 91%. This indicates that the introduction of Fe reduces the adsorption energy of Pt for CO to a certain extent, thereby increasing the CO tolerance of the catalyst.

[0061] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A method for preparing an anode catalyst, characterized in that: The preparation method is specifically as follows: solid phase synthesis method is used to prepare KCa2Nb3O 10 Then acid replacement was performed to obtain HCa2Nb3O 10 ; Prepare Pt3Fe / EC and react with HCa2Nb3O 10 The mixture is ball-milled and then dried to obtain the anode catalyst.

2. The method for preparing an anode catalyst according to claim 1, characterized in that: KCa2Nb3O 10 The preparation method is as follows: K2CO3, CaCO3 and Nb2O5 are mixed in a mass ratio of (0.5-1.2):(1.5-3):(3-6), ball milled at 200-500 rpm for 0.5-2h and then dried, calcined at 1000-1500°C for 10-15h, ground, and re-fired at 1000-1500°C to obtain.

3. The method for preparing an anode catalyst according to claim 1, characterized in that: KCa2Nb3O 10 Acid replacement to obtain HCa2Nb3O 10 The specific method is: according to the ratio of (2-5) g: (80-150) ml, KCa2Nb3O 10 The product is immersed in 5-10 mol / L HCl at room temperature for 40-50 hours, and the HCl is replaced once every 20-25 hours, and then centrifuged and dried at 60-80°C.

4. The method for preparing an anode catalyst according to claim 1, characterized in that: The preparation method of Pt3Fe / EC includes an impregnation method or a two-step method; wherein the specific method of the impregnation method is: dispersing ferric nitrate nonahydrate, chloroplatinic acid, and PVP in an EC aqueous solution, heating and stirring until dry, and calcining the obtained powder in a hydrogen and argon atmosphere to obtain Pt3Fe / EC; The specific method of the two-step method is: disperse a Pt / C catalyst with a Pt content of 20-40wt% and ferric nitrate nonahydrate in deionized water, adjust the pH to 9-10.5 with ammonia water, and then centrifuge, dry, and calcine in a hydrogen and argon atmosphere to obtain Pt3Fe / EC.

5. The method for preparing an anode catalyst according to claim 4, characterized in that: In the impregnation method, the ratio of ferric nitrate nonahydrate, chloroplatinic acid, PVP, EC and water is (20-30) mg: (7-12) ml: (100-150) mg: (50-70) mg: (20-50) ml, and the mass concentration of platinum in chloroplatinic acid is 2-7 mg. Pt / ml; The conditions for heating and stirring are: 70-90°C; The calcination conditions are: 850-1000°C, 1.5-3h.

6. The method for preparing an anode catalyst according to claim 4, characterized in that: In the two-step method, the ratio of Pt / C catalyst, ferric nitrate nonahydrate and deionized water is (180-250) mg: (45-60) mg: (30-80) ml; Drying conditions: 60-80℃, 20-30h; The calcination conditions are: 850-1000°C, 1.5-3h.

7. A method for preparing a membrane electrode, characterized in that: The anode catalyst prepared by any method described in claim 1-6, 5wt% Nafion solution and conductive carbon are dispersed in an alcohol solution in a mass ratio of 1:(5-8):(0.3-1.2) to prepare an anode slurry, and then the anode slurry is sprayed on an electrolyte membrane at 70-85°C and hot-pressed to obtain the anode slurry.

8. Use of the membrane electrode according to claim 7 as an anode in a proton exchange membrane fuel cell.

9. Application of Fe doping in improving CO tolerance of proton exchange membrane fuel cells, characterized in that: The CO tolerance of the anode catalyst is enhanced by doping Fe into the anode catalyst, adjusting the electronic structure of Pt by Fe, and reducing the adsorption energy of Pt for CO.